Paramagnetic, NIR‐luminescent Nd3+‐ and Gd3+‐doped fluorapatite as contrast agent for multimodal biomedical imaging. Issue 10 (14th May 2018) - Tesch, Annemarie; Röder, Robert; Zapf, Maximilian; Ronning, Carsten; Warncke, Paul; Fischer, Dagmar; Herrmann, Karl‐Heinz; Reichenbach, Jürgen R.; Müller, Frank A.
Abstract: Combining near infrared (NIR) luminescence and magnetic resonance (MR) contrasts in a crystal host is highly desirable for contrast agents in biomedical imaging technology, as it will enable multimodal imaging processes. In the present work, biocompatible luminescent and paramagnetic fluorapatite (FAp) nanoparticles were prepared via doping with neodymium (Nd 3+ ) and gadolinium (Gd 3+ ), respectively. While Nd 3+ ‐doped FAp (Nd:FAp) exhibits dopant concentration‐dependent photoluminescence (PL) in the NIR spectral region, Gd 3+ ‐doped FAp (Gd:FAp) shows paramagnetic behavior and strong transverse relaxation effects resulting in MR contrastive properties. Remarkably, multimodal co‐doped FAp (Nd:Gd:FAp) nanoparticles combine both properties in 1 single crystal enabling luminescence as well as MR contrast.